2018
DOI: 10.1186/s42408-018-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Historical and modern landscape forest structure in fir (Abies)-dominated mixed conifer forests in the northern Sierra Nevada, USA

Abstract: Background: Information about fire and historical forest structure and composition in fir-dominated mixed conifer forests is lacking, especially at the landscape scale. This study used historical timber survey data to characterize early forest conditions in a large fir-dominated northern Sierra Nevada landscape (area >10 000 ha). We used automated model selection to determine the suite of environmental variables that best predicted forest structure, and regression tree analysis to identify environmental settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
4
20
3
Order By: Relevance
“…This article is protected by copyright. All rights reserved Collins et al 2015, 2018cBattaglia et al 2018Johnston et al 2018 Consistent with the finding that Williams and Baker (2011) methods overestimate tree density (Levine et al 2017, Johnston et al 2018, Knight et al 2020, early timber inventory records and treering reconstructions for the same study areas documented substantially lower tree densities than those estimated using Williams and Baker (2011) methods…”
Section: Accepted Articlesupporting
confidence: 68%
“…This article is protected by copyright. All rights reserved Collins et al 2015, 2018cBattaglia et al 2018Johnston et al 2018 Consistent with the finding that Williams and Baker (2011) methods overestimate tree density (Levine et al 2017, Johnston et al 2018, Knight et al 2020, early timber inventory records and treering reconstructions for the same study areas documented substantially lower tree densities than those estimated using Williams and Baker (2011) methods…”
Section: Accepted Articlesupporting
confidence: 68%
“…When compared to mixed-conifer reference conditions outside the southwest, our results are similar to those found on the Front Range of northern Colorado and southern Wyoming [74,75], and considerably less dense than the results reported from some parts of the Sierra Nevada in California [76]. Historical conditions from other parts of the Sierra Nevada [33,77,78] and mountains in Oregon [79][80][81] had higher basal area and lower tree density than in our study area, suggesting that those forests had fewer and larger trees than those found on the Mogollon Rim.…”
Section: Historical Range Of Variabilitysupporting
confidence: 83%
“…Historical logging targeted large, commercially valuable trees, which may have been concentrated on lower, more productive microsites. While density has increased significantly across the entire study area, Rodman et al [23] and Stephens et al [33] both found that density increases were greatest on mesic sites such as valleys and lower slopes. The increase in density on the Mogollon Rim sites was also related to compositional changes.…”
Section: Drivers Of Variabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…2015, Stephens et al. 2015, 2018). The inventories were largely conducted prior to the major structural and compositional changes associated with later 20th‐century land use practices including widespread grazing, logging, and fire suppression (Safford and Stevens 2017), supporting their use as reference conditions for forest restoration.…”
Section: Introductionmentioning
confidence: 99%